MiR‐183 and miR‐96 orchestrate both glucose and fat utilization in skeletal muscle. (6th August 2021) - Wang, Hui; Ma, Mei; Li, Yuying; Liu, Jinxin; Sun, Chao; Liu, Shengnan; Ma, Yiruo; Yan, Ying; Tang, Zhili; Shen, Siyi; Yu, Jing; Wu, Yuting; et al.
Abstract: Our knowledge of the coordination of fuel usage in skeletal muscle is incomplete. Whether and how microRNAs are involved in the substrate selection for oxidation is largely unknown. Here we show that mice lacking miR‐183 and miR‐96 have enhanced muscle oxidative phenotype and altered glucose/lipid homeostasis. Moreover, loss of miR‐183 and miR‐96 results in a shift in substrate utilization toward fat relative to carbohydrates in mice. Mechanistically, loss of miR‐183 and miR‐96 suppresses glucose utilization in skeletal muscle by increasing PDHA1 phosphorylation via targeting FoxO1 and PDK4. On the other hand, loss of miR‐183 and miR‐96 promotes fat usage in skeletal muscle by enhancing intramuscular lipolysis via targeting FoxO1 and ATGL. Thus, our study establishes miR‐183 and miR‐96 as master coordinators of fuel selection and metabolic homeostasis owing to their capability of modulating both glucose utilization and fat catabolism. Lastly, we show that loss of miR‐183 and miR‐96 can alleviate obesity and improve glucose metabolism in high‐fat diet‐induced mice, suggesting that miR‐183 and miR‐96 may serve as therapeutic targets for metabolic diseases. Synopsis: miR‐183 and miR‐96 are critical for maintaining the oxidative phenotype of skeletal muscle and whole‐body homeostasis. They regulate fuel selection by coordinating glucose usage and fat catabolism via FoxO1, PDK4 and ATGL in skeletal muscle. Mice lacking miR‐183 and miR‐96 exhibit altered fuel utilization and glucose and lipid homeostasis. miR‐183 and miR‐96 promote glucose usage via FoxO1‐PDK4‐PDH axis in skeletal muscle. miR‐183 and miR‐96 repress intramuscular lipolysis and fatty acid oxidation by targeting ATGL. Loss of miR‐183 and miR‐96 ameliorates the deleterious effects of HFD feeding. Abstract : miR‐183 and miR‐96 are critical for maintaining the oxidative phenotype of skeletal muscle and whole‐body homeostasis. They regulate fuel selection by coordinating glucose usage and fat catabolism via FoxO1, PDK4 and ATGL in skeletal muscle.